The Berenstain Bears clean house - Berenstain, Stan, 1923-2005.; Berenstain, Jan, 1923- (New York : HarperCollins, 2005)
When Mama, Papa, Sister, and Brother decide to clean their house, they find that it is difficult to get rid of things.
1.9
K-3.
K-3
Keywords: Bears -- Juvenile fiction; Berenstain Bears (Fictitious characters) -- Juvenile fiction; House cleaning -- Juvenile fiction; Bears -- Fiction; Berenstain Bears (Fictitious characters) -- Fiction; House cleaning -- Fiction; Bears -- Fiction; Berenstain Bears (Fictional characters) -- Fiction; House cleaning -- Fiction; Readers (Elementary).